PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. BNI LIFE INSURANCE JAKARTA SELATAN - Zama Razif; Asep Sulaeman (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of motivation and work discipline on employee performance at PT. BNI Life Insurance, South Jakarta, either partially or simultaneously. This research method uses quantitative methods, with a sample size of 60 respondents. The data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression test, simultaneous correlation coefficient test, simultaneous coefficient of determination test. simultaneous, t test and f test. Based on the t test, the value obtained is tcount > ttable (3.143>1.672) and the significance value is 0.003 <0.05. This means that motivation (X1) has a significant effect on employee performance (Y). Partially testing the hypothesis for the work discipline variable (X2) obtained a value of tcount > ttable (3.523>1.672) and a significance value of 0.001 <0.05. This means that work discipline (X2) has a significant effect on employee performance (Y). Simultaneous hypothesis testing obtained a value of fcount > ftable (71.720>3.16) and a significance value of 0.000 <0.05. So it can be concluded that motivation (X1) and work discipline (X2) have a significant simultaneous effect on employee performance (Y).